Linear and volumetric parameters of left atrium in patients with isolated aortic stenosis - G. E. Gendlin; A. I. Kovaleva; E. I. Emelina; I. G. Nikitin (Российский кардиологический журнал)
Aim. To study volumetric and linear parameters of the left atrium (LA) in operated and non-operated patients with severe  aortic stenosis  (AS) in comparison  with the control group of a similar age and gender.Material and methods. Eighty-one patients with AS were examined, 49 patients — in the long term after aortic valve replacement (AVR), and 30 patients of similar age and gender  — without a heart defect.  Echocardiography  was performed  using an Acuson Sequia 512 ultrasound scanner.Results. The volumetric parameters of LA (LA volume index (LAVI)) and the ratio of the  minimum LA  with LV  volume at  this time point (LAVmin/LV)  were  the  most sensitive  parameter when  evaluating  the  LV  diastolic  function  in patients  with isolated AS when comparing  non-operated and operated patients  and the control group. The study of association of non-operated AS patients with LAVI (greater than or less than 32 ml/m2) showed only a slight divergence  between the Kaplan-Meyer curves with a log-rank test of 0,15. Only the values of the LV ejection fraction (LVEF) differed from parameters of died (n=21) and alive patients at the time of the study (n=60): 61,0 (56,4-69,3)% in alive versus 46,4 (39,1-55,4)% in dead ones (p<0,0001). The time elapsed from the diagnosis to the date of the examination also differed: 0,5 (0,4-11,0)  years  in alive versus  7,0 (3,0-19,0)  years  in dead  ones  (p=0,004).  With multiple regression, the  highest  and  statistically significant beta  coefficient  was found only in LVEF (beta — -0,52, p=0,002).Conclusion. Linear and volumetric parameters of LA slightly associate with the age and  gender   of  operated  and  non-operated  AS patients.   These   parameters statistically  significantly differ in the  groups  of non-operated AS patients  and patients after AVR compared with the control group, including patients without heart disease. The values of linear and volumetric LA parameters in patients with AS after AVR are close to those in the control group.